Coiled coil peptides and polymer-peptide conjugates: synthesis, self-assembly, characterization and potential in drug delivery systems - Pechar, Michal; Pola, Robert; Laga, Richard; Braunová, Alena; Filippov, Sergey K; Bogomolova, Anna; Bednárová, Lucie; Vaněk, Ondřej; Ulbrich, Karel (Biomacromolecules, 2014)
Coiled coils are a common structural motif in many natural proteins that can also be utilized in the design and preparation of drug delivery systems for the noncovalent connection of two macromolecules. In this work, two different pairs of peptides forming coiled coil hetero-oligomers were designed, synthesized, and characterized. While the peptide sequences (VAALEKE)4 and (VAALKEK)4 predominantly form coiled coil heterodimers with randomly orientated peptide chains, (IAALESE)2-IAALESKIAALESE and IAALKSKIAALKSE-(IAALKSK)2 tend to form higher hetero-oligomers with an antiparallel orientation of their peptide chains. The associative behavior of these peptides was studied in aqueous solutions using circular dichroism spectroscopy, size-exclusion chromatography, isothermal titration calorimetry and sedimentation analyses. The orientation of the peptide chains in the coiled coil heterodimers was assessed using fluorescence spectroscopy with fluorescence resonance energy transfer labels attached to the ends of the peptides. The formation of the heterodimer can be used as a general method for the selective noncovalent conjugation of a specific targeting moiety with various drug carrier systems; this process involves simple self-assembly in a physiological solution before drug administration. The preparation of targeted macromolecular therapeutics consisting of a synthetic polymer drug carrier and a recombinant protein targeting ligand is discussed.
Keywords: Oligopeptides; sekvence aminokyselin; Solid-Phase Synthesis Techniques; Amino Acid Sequence; Protein Structure, Secondary; nosiče léků; methakryláty; oligopeptidy; sekundární struktura proteinů; techniky syntézy na pevné fázi; Drug Carriers; Methacrylates